Miniaturized Wideband Bandpass Filter based on Capacitor-loaded One-eighth Wavelength Coupled Line - Shi, Jin; Dong, Jiancheng; Xu, Kai; Zhang, Lingyan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel miniaturized wideband bandpass filter (BPF) using capacitor-loaded microstrip coupled line is proposed. The capacitors are loaded in parallel and series to the coupled line, which makes the filter just require one one-eighth wavelength coupled line and achieve filtering response with multiple transmission poles (TPs) and transmission zeros (TZs). Compared with the state-of-the-art microstrip wideband BPFs, the proposed filter has the advantages of compact size and simple structure. A prototype centered at 1.47 GHz with the 3-dB fractional bandwidth of 86.5% is demonstrated, which exhibits the compact size of 0.003λ2/g (λg is the guided wavelength at the center frequency) and the minimum insertion loss of 0.37 dB.